Corresponding Changes in Sleep and Discrimination: A Three-year Longitudinal Study Among Ethnically/Racially Diverse Adolescents. - Lorenzo, Kyle; Xie, Mingjun; Cham, Heining; El-Sheikh, Mona; Yip, Tiffany (Journal of Youth & Adolescence, 2025)
Although research has established the immediate, detrimental impact of discrimination on sleep, how changes in experiences of discrimination may be related to changes in sleep duration over multiple years is less clear. This three-year longitudinal study investigated: (1) intercept-only and linear trajectories of sleep and everyday discrimination across three years of high school; (2) ethnic/racial differences in these trajectories; and (3) the associations between changes in sleep and changes in everyday discrimination. The sample consisted of ethnically/racially minoritized adolescents from five northeast U.S. public high schools (n = 329; 70% female, 30% male, 0% non-binary; 42% Asian, 21% Black, 37% Latiné; M = 14.72, SD = 0.54). Latent growth curve models found that both sleep duration and everyday discrimination declined linearly throughout the first three years of high school and varied by race/ethnicity. Asian adolescents reported longer sleep duration in the 9th grade relative to Black and Latiné adolescents but underwent a significant decline such that these differences were no longer significant in the 10th and 11th grades. In addition, Black and Latiné, but not Asian, adolescents reported a significant decline in discrimination from the 9th–11th grades. Although average sleep duration declined for the entire sample, slower declines in discrimination were associated with faster decreases in sleep duration. This was particularly salient among Black adolescents. The current study contributes to research on ethnic/racial disparities in sleep by highlighting that everyday discrimination can have both an immediate and cumulative detrimental impact on sleep duration.